Modrave – looking for traces of the past in a dry-stone wall maze (In situ, 2024)
An unusual segment of the Adriatic coast extends between Zadar and Šibenik. On one side is the Adriatic Sea, and on the other is Lake Vrana, the largest lake in Croatia, with a low isthmus in between. An aerial view of this area shows two different parts - in the northwest is a network of cultivated and wooded plots of different sizes, scrub, settlements and roads, in the southeast is a mosaic of small plots covered with vegetation. Few of them are cultivated, there is a lot of scrub, some buildings and a series of lines, rarely roads, often dry stone walls. The toponym Modrave refers exactly to that mosaic. The absence of settlements and straight road are a sign to today's travelers to speed up with the foot on the gas, without even having time to think about what the Mediterranean scrub around them is hiding. But it was not always like that. The mosaic of dry stone walls and overgrown olive groves has been abandoned by humans, yet it is full of traces of their activity from different times.
Keywords: Modrave; cultural landscape; archaeological survey; dry-stone